Analysis of Entrepreneurship Education on Entrepreneurship Attitude Students Economic Education Department Faculty of Economic Manado State University - Wuisang, Jerry RH; Korompis, Consuslasia; Lempas, Jetty D. (Asia Pacific Journal of Management and Education (APJME), 2019)
This study aims to determine the effect of Entrepreneurship Education on Entrepreneurship Attitudes of Students of Economic Education Department at the Faculty of Economics, Manado State University. With the independent variable namely Entrepreneurship Education and the dependent variable is the Attitude of Entrepreneurship. This research was conducted on some students in the Faculty of Economics, Manado State University Economic Education Department. The sample in this study were 60 students of the Faculty of Economics, Manado State University Economics Education Department. The problem in this research is trying to identify the factors that cause the Student Entrepreneurship Attitude to be still low, whether the process of entrepreneurship education is not maximized so that the Attitude of Student Entrepreneurship is low. The research objective was to see the effect of Entrepreneurship Education on increasing the Attitude of Student Entrepreneurship in the Economics Education Department at the Faculty of Economics, Manado State University. The research method used is a survey with data analysis techniques is regression correlation. The results showed that there was an influence of Entrepreneurship Education with the Attitude of Student Entrepreneurship. This, can be seen from the observation and the results of the analysis of the correlation coefficient between the two variables, namely the variable X as Entrepreneurship Education and variable Y as the Attitude of Student Entrepreneurship. Where analysis uses simple regression Å¶ = 44,99 + 0,06 X, and analysis using product moment correlation shows value r = 0,5 dan r2 = 0,25 atau 25%. While testing the significant level of the correlation coefficient using the t test with a real level 5% (Î± = 0,5) obtained thitung = 3,05 dan ttabel = 2,05 this means thitung < dari ttabel. These results can be understood that Entrepreneurship Education can improve Student Entrepreneurship Attitudes in the learning process which will ultimately improve student outcomes. With the existence of Entrepreneurship Education, it will affect the Attitude of Entrepreneurship in Students of the Economic Education Department at the Faculty of Economics, Manado State University.